Science Literacy Aspects of Environmental Awareness of Fifth-Grade Students Influenced by The Creative Problem-Solving (CPS) Learning Model - Ni Komang Sintya Dewi; Desak Putu Parmiti; Basilius Redan Werang (Universitas Pendidikan Ganesha, 2024)
Indonesia's literacy condition is fragile, which is indicated by the low scientific literacy of students. This study was conducted to determine the effect of the Creative Problem Solving (CPS) learning model on scientific literacy in the environmental awareness aspect of fifth-grade elementary school students. This study is a quasi-experimental type using a posttest-only control group design. A total of 171 students comprised the research population, from fifth-grade elementary school students. A total of 47 students were selected as samples through random sampling techniques. In obtaining research data, a non-test method was used in the form of a questionnaire to measure scientific literacy in terms of environmental awareness. Data analysis was obtained through t-test analysis or independent sample t-test. This study shows the results that there is an effect of the Creative Problem Solving (CPS) model on scientific literacy in the environmental awareness aspect of fifth-grade elementary school students (t equals 10.198, p less than 0.05) with a relatively high effect size (ES 1.48). So, it is concluded that the Creative Problem Solving (CPS) model positively affects scientific literacy in the environmental awareness aspect of fifth-grade elementary school students. The implications of this study can develop student creativity in various learning packages.